A virtual screening and molecular dynamics approach in search of novel antibiotic chemotypes - Tahira Noor; Daniel C. Schultz; Yuting Zhai; Hannah E. Snoke; Suyeun Noh; Gustavo Seabra; Richard E. Lee; Kwangcheol Casey Jeong; Chenglong Li; Abdul Rauf Siddiqi (PLoS ONE, 2026)
Due to the constantly evolving threat of antibiotic resistance, there is a dire need for novel antibacterial agents. Dihydropteroate synthase (DHPS) is a key bacterial enzyme which has been targeted for nearly a century as a means of selective treatment of microbial infections and exhibits two orthosteric binding sites – the p -aminobenzoic acid ( p ABA) site and the pterin site. The former is the target of sulfonamides, the earliest class of synthetic antibiotics, and its mutant forms have conferred resistance to this drug class, diminishing its utility in the clinic. Conversely, the pterin site, which is highly conserved across bacterial species, is purported to be less tolerant of mutations, rendering it an attractive target for novel antibiotics. Inspired by this, we conducted a large virtual screen of more than 450,000 compounds from commercial databases, identifying compounds 8802 and 7034 as potential pterin-site inhibitors. Compound 8802 was quite attractive as a hit due to the ease of generating analogues, leading to the synthesis of novel compounds LST-1 and LST-2 . Rigid docking and molecular dynamics suggested favorable binding of these compounds to the pterin site of DHPS, and compound 8802 exhibited superior antibacterial activity compared to its analogues and 7034 . Fluorescence polarization assays did not indicate competitive inhibition of pterin-derived probe binding, and surface plasmon resonance (SPR) suggested these compounds bind very weakly to DHPS, in a nonspecific manner. The in silico assessment of the physicochemical and pharmacological properties predicted a favorable overall profile, indicating that these are suitable leads for further study to improve their activity and determine their precise mode of action.